Digital Comic Design as an Educational Medium on the Dangers of Online Gambling - Ahmad Albar; Ade Moussadecq (IMAGIONARY, 2025)
The widespread practice of online gambling among adolescents in Lampung has created serious economic, psychological, and moral impacts. Easy access via smartphones and social media makes youth vulnerable, while government efforts such as blocking and law enforcement remain insufficient. This study aims to design digital comics as an educational medium on the dangers of online gambling tailored to young audiences. A qualitative method was applied through observation, literature review, and interviews with the Central Bureau of Statistics (BPS) of Lampung. The design process included pre- production, production, and post-production, involving character development, scripting, coloring, and Instagram publication. Trial results showed that digital comics effectively enhanced audience understanding, indicated by strong engagement and positive responses. The findings confirm that digital comics serve as a communicative and adaptive educational medium, offering an appealing approach to raise awareness and prevent youth involvement in online gambling.